Immunostimulant Activity of Moringa Leaves (Moringa Oleifera Lam.) Combined with Lime Peel (Citrus Aurantifolia) in Vitro - Tenda, Priska Ernestina; Ramadhani, Arba Pramundita (Journal of World Future Medicine, Health and Nursing, 2024)
Moringa leaves (Moringa Oleifera Lam.) are known to have many chemical contents such as vitamin A, vitamin C, flavonoids, phenolic compounds, carotenoids, tannins and triterpenoids with high uses, one of which is as an immunostimulant. Previous researchers reported that moringa leaves have been developed in various preparations but have not been able to cover the problem of the smell and taste of moringa leaves that are less accepted by consumers. In this study, moringa leaves were combined with lime peel ginger (Citus aurantifolia) to cover the taste and smell of moringa leaves. This study aims to determine the immunostimulant activity of moringa and lime peel in three formulas.  Formula F1= moringa:lime peel (1:1); F2= moringa:lime peel (2:1) F3= moringa:lime peel (3:1); F4= moringa extract. The research conducted was experimental research with the research design used was a completely randomised design and three different treatments with three repetitions. Each treatment was repeated 3 times so that 12 experimental units were obtained. Statistical analysis using the probit test. The results of plant identification showed true moringa leaves and lime peel with chemical content of flavonoids, tannins, terpenoids, alkaloids, saponins based on the results of colour recreation. The IC50 value of immunostimulant activity test of the best formula of tea as immunostimulant is F4, F3, F2 and F1 respectively: 701.83 ± 113.36; 701.83 ± 113.36; 488.08 ± 139.60; 488.08 ± 139.60 µg/mL. Overall, the formulas have the potential to be developed as immunostimulants.